1999
DOI: 10.1002/(sici)1097-0363(19991130)31:6<911::aid-fld905>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Parallel solution of three-dimensional Marangoni flow in liquid bridges

Abstract: This paper describes the implementation and performances of a parallel solver for the direct numerical simulation of the three-dimensional and time-dependent Navier Stokes equations on distributed-memory, massively parallel computers. The feasibility of this approach to study Marangoni flow instability in half zone liquid bridges is examined. The results indicate that the incompressible, non linear Navier-Stokes problem, governing the Marangoni flows behaviour, can effectively be parallelized on a distributedm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…For cylindrical liquid bridges previous numerical computations ( [7][8][9][10][11]) have shown that the flow structure of the supercritical state depends on the value of the aspect ratio of the liquid bridge. The lower the aspect ratio, the higher the azimuthal wave number m resulting in the more complex flow organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For cylindrical liquid bridges previous numerical computations ( [7][8][9][10][11]) have shown that the flow structure of the supercritical state depends on the value of the aspect ratio of the liquid bridge. The lower the aspect ratio, the higher the azimuthal wave number m resulting in the more complex flow organization.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating over the generic control volume and using the Gauss theorem to transform volume integrals in surface integrals, the equations read The problem is solved with the well known Marker and Cell method (see e.g. Lappa and Savino [10] and Fletcher [25]). …”
Section: Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward differences in time and central-differencing schemes in space (second order accurate) have been used to discretize the energy and momentum governing equations. The related solution strategy is not discussed here, the interested reader being referred to various books and articles in the literature for an exhaustive treatment (for the implementation of this method on parallel machines, the reader may consider, e.g., Lappa and Savino, 1999;Lappa, 2003a and2004). The above statement, however, does not apply to the part concerning the computation of PAS with equations (14), which was not validated in earlier studies of the present author (both Lappa, 2013a and2013b, in fact, were based on a simplified version of the Maxey-Riley equation, the so-called inertial equation).…”
Section: Solution Methods and Validation Studymentioning
confidence: 99%
“…More precisely, at each time step, an intermediate velocity field is determined without the knowledge of the correct pressure field, and therefore no incompressibility condition is enforced. The intermediate velocity field is then modified by a second step in which a pressure equation is solved and then the related results are used to produce a divergence-free vector field 42 .…”
Section: A Projection Methodsmentioning
confidence: 99%